How innovation works : and why it flourishes in freedom - Ridley, Matt (Harper, an imprint of HarperCollinsPublishers, 2020)
Building on his national bestseller The Rational Optimist, Innovation is the main event of the modern age, the reason we experience both dramatic improvements in our living standards and unsettling changes in our society. Forget short-term symptoms like Donald Trump and Brexit, it is innovation that will shape the twenty-first century. Yet innovation remains a mysterious process, poorly understood by policy makers and businessmen alike. Matt Ridley argues that we need to see innovation as an incremental, bottom-up, fortuitous process that happens as a direct result of the human habit of exchange, rather than an orderly, top-down process developing according to a plan. Innovation is crucially different from invention, because it is the turning of inventions into things of practical and affordable use to people. It speeds up in some sectors and slows down in others. It is always a collective, collaborative phenomenon, involving trial and error, not a matter of lonely genius. It happens mainly in just a few parts of the world at any one time. It still cannot be modeled properly by economists, but it can easily be discouraged by politicians. Far from there being too much innovation, we may be on the brink of an innovation famine. Ridley derives these and other lessons from the lively stories of scores of innovations, how they started and why they succeeded or failed. Some of the innovation stories he tells are about steam engines, jet engines, search engines, airships, coffee, potatoes, vaping, vaccines, cuisine, antibiotics, mosquito nets, turbines, propellers, fertilizer, zero, computers, dogs, farming, fire, genetic engineering, gene editing, container shipping, railways, cars, safety rules, wheeled suitcases, mobile phones, corrugated iron, powered flight, chlorinated water, toilets, vacuum cleaners, shale gas, the telegraph, radio, social media, block chain, the sharing economy, artificial intelligence, fake bomb detectors, phantom games consoles, fraudulent blood tests, hyperloop tubes, herbicides, copyright, and even life itself.